Consumer Motivation, Product Quality, and After-Sales Service Affecting Purchase Decision (Study on Consumer of Used Car in Bekasi) - Widasari, Hanna Vania; Azzuhri, Misbahuddin (Jurnal Ilmiah Mahasiswa FEB, 2016)
Car automotive industry currently has develop more widely with the production segment which more creative and dynamic. Indonesian society needs to the four-wheeled has increasing from year to year. Consumer behavior in determining the decision to have a car becomes more varied, a lot of things that are interest to the type of car they want to buy, from the brands, models, specification, price, after-sales service, resale price, and others including  popular  trends  on  the  brand  and  type  of  car  at  the  time.  It  all  creates  the motivation of consumer to make purchasing decision. The purpose of this research is to analyze the influence of consumer motivation, product quality, and after-sales service toward purchasing decision. The object of this research is product of used cars’ user around Bekasi. This research involves 110 people as its respondents.  Author  distributes  questionnaires  for data  collection  and  analyzes  it  with double-regression linear analysis by SPSS software. The regression analysis, F test and t test, were conducted in  order to acknowledge the relationship  among  the independent variables that is Consumer motivation, Product Quality, and After-Sales Service on Purchasing Decision. The sampling technique used is Purposive sampling and the research instruments were tested using validity test, reliability test, and classical assumption test. The multiple regression analysis in this research showed that simultaneously, Consumer Motivation, Product quality, and After-Sales Service had significant effect on Purchasing Decision. Meanwhile, partial test shows that the variables of Consumer Motivation, Product quality, and After-Sales Service had significant effect on Purchasing Decision.   Keywords: Consumer  Motivation,  Product  Quality,  After-Sales  Service,  Used  Car